DESAIN.PEMBANGKIT.LISTRIK.TENAGA SURYA.(PLTS).MENGIKUTI.POLA.ATAP WANTILAN.DESA.ANTOSARI.UNTUK MEMENUHI.DAYA.3600.WATT - Wiradhi Yogathama, I Gusti Bagus; Arta Wijaya, I Wayan; Budiastra, I Nyoman (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
The design of the solar power plant (PLTS) at the Antosari village wantilan is a research that aims to realize the use of new and renewable energy which is one of the solutions in overcoming electricity needs, saving fossil energy and assisting in the realization of Governor Regulation 45/2019 concerning Bali Clean Energy. This study carried out the design and calculations in the design of the PLTS Atap Antosari Village. The PLTS design is carried out by paying attention to and taking into account the tilt angle of the Helioscope Software, designing the placement of the solar panel modules, designing the inverter, configuring the circuit, taking into account the number of batteries used, selecting the Battery Control Unit and calculating the profit on investment. The results of the simulation on the helioscope software are the number of solar modules as many as 72 units, installed at an angle of 14.95o which can supply a battery with a capacity of 500Ah. The simulation also determines the use of an inverter that uses a 4kW inverter which produces a power of 3.6 kWp. The ability of the installed solar module to flow a current of 97.56A so that the full charge condition is obtained for 6 hours. Research initial capital of Rp. 201,400,000 with a return of Rp. 1,325,376, - per month, so that the financing for installing PLTS will return in 2034 (13 years)